Optimal Location of UPFC with ATC Calculation - Salim, Norhafiz (Scientifiec.net, 2013)
Flexible AC Transmission System (FACTS) devices namely Unified Power Flow Controller (UPFC) will gives a basic control for transmission line real/reactive power flow and bus voltage/shunt reactive power. UPFC helps in regulating the power and mitigating the rotor speed instability and damping oscillations. UPFC placement was conducted at each line in the entire network system to obtain the most suitable optimum location for most effectiveness performance. The performance of the optimal UPFC location is checked by applying a fault across a transmission line to which UPFC is connected and the power flow in the line and stability of the system is determined. Available Transfer Capability values indicate allowable highest magnitude of active power (MW) that can be transferred from the source to the sink over and above the already committed uses (base case) of the whole network without exceeding any line thermal loading and bus voltage limits. Finally, simulations were carried out using PSAT software to validate the performance of the UPFC which connected to a transmission line. The effectiveness for UPFC is demonstrated on IEEE 9 bus and IEEE 24 bus system while for ATC is demonstrated on IEEE 6 bus system and all the results are compared.